Estimating the potential of sustainable aviation fuel enabled aviation decarbonization in China: An integrated resource-technology-economy-environment analysis framework - Yan, Wubin; Cheng, Fangwei; Wang, Xiaonan; Zhang, Chuan (Computer Aided Chemical Engineering, 2024)
The decarbonization of aviation sector has aroused extensive attention in China. Sustainable aviation fuel is widely considered as a promising strategy for aviation decarbonization. However, a realistic estimation of China's sustainable aviation fuel enabled decarbonization potential has not been achieved so far. In order to fill this gap, system analysis including resource potential evaluation, conversion process simulation, techno-economic analysis, and environmental impact assessment are conducted to evaluate the decarbonization potential of sustainable aviation fuel in China's aviation sector. In this study, sustainable aviation fuel is produced from six conventional crop straws in China via Gasification-Fischer-Tropsch conversion pathway. Among these straws, cotton straw and corn straw are promising feedstocks for sustainable aviation fuel production from the perspective of decarbonization cost. Considering their reserves in China, cotton straw is suitable for early industrial production of sustainable aviation fuel, while corn straw can support future large scale sustainable aviation fuel application. When the blending ratio of sustainable aviation fuel reaches 50 %, about 60 Mt CO2e emission can be reduced, which accounts for 43 % of the emission for China's aviation sector in2023, showing the huge decarbonization potential of sustainable aviation fuel.